2021
DOI: 10.3390/polym13173006
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology and Mechanical Properties of Polyether Ether Ketone (PEEK) Nanocomposites Reinforced by Nano-Sized Silica (SiO2) for Prosthodontics and Restorative Dentistry

Abstract: In the field of orthopedics and traumatology, polyether ether ketone (PEEK) serves a significant role as a suitable alternative to traditional metal-based implants like titanium. PEEK is being used more commonly to replace traditional dental products. For bonding with various adhesive agents and preserved teeth, the surface alteration of PEEK was investigated. The aim of this research was to understand how different types and contents of nano-sized silica (SiO2) fillers influenced the surface and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…We found that the tensile strength of the PLA/ZnO biocomposite filaments gradually decreased with increasing ZnO nanoflower contents ( Figure 6 a). The PLA/ZnO-5 encountered a decrease in tensile strength because of the higher ZnO nanoflower contents, caused by filler agglomeration during the melt extrusion process, resulting in poor interfacial adhesion of particles and matrix [ 39 , 40 ]. From Table 2 , the modulus strength of the PLA/ZnO biocomposite filaments decreased when the ZnO nanoflower contents increased.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the tensile strength of the PLA/ZnO biocomposite filaments gradually decreased with increasing ZnO nanoflower contents ( Figure 6 a). The PLA/ZnO-5 encountered a decrease in tensile strength because of the higher ZnO nanoflower contents, caused by filler agglomeration during the melt extrusion process, resulting in poor interfacial adhesion of particles and matrix [ 39 , 40 ]. From Table 2 , the modulus strength of the PLA/ZnO biocomposite filaments decreased when the ZnO nanoflower contents increased.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocomposites have recently been used enormously in the dentistry field. For the treatment of oral disorders, they may be utilized as drug delivery systems, fillers, restorative substances, and tissue engineering components [ 17 , 18 , 19 ]. Fiber nanocomposites have a high surface-to-volume ratio, owing to their fiber shape.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear as to which fabrication method is best for PEEK in prosthetic dentistry, and this is another area that requires further development. It is known that the superior performance exhibited by PEEK in fixed restorations can be further improved by adjusting the properties of PEEK via glass-or carbon-fiber reinforcement (GFR-PEEK, CFR-PEEK) [21,109], particle filling (nano-sized silica, titanium dioxide, nano-hydroxyapatite, amorphous magnesium phosphate) [110][111][112][113][114][115], and coating (titanium, methyl methacrylate, polymethyl methacrylate, polydopamine) [67,116,117]. Some of these materials have also been shown to improve the bonding strength of PEEK [67,113,117].…”
Section: Future Perspectivementioning
confidence: 99%